2005
DOI: 10.1007/s10725-005-5901-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth, photosynthetic capacity and ionic relations in spring wheat (Triticum aestivum L.) due to pre-sowing seed treatment with polyamines

Abstract: The influence of pre-sowing seed treatment with polyamines (2.5 mM putrescine, 5.0 mM spermidine and 2.5 mM spermine) on growth, photosynthetic capacity, and ion accumulation in two spring wheat (Triticum aestivum L.) cultivars MH-97 (intolerant) and Inqlab-91 (tolerant) was examined. The primed seeds of each treatment and non-primed seeds were sown in a field containing 15 dS m À1 NaCl. Although all three polyamines were effective in improving shoot growth and grain yield in both cultivars under saline condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 39 publications
5
32
0
1
Order By: Relevance
“…Our results are in agreement with the findings of Krauss and Allen (2003), suggesting that salinity negatively affects the efficiency of solar energy utilization in S. argentea seedlings. The close relationship between P N and Na + concentration in leaf tissue was reported by Iqbal and Ashraf (2005), indicating that P N was affected by Na + in the leaf mesophyll. Salinity-induced excessive accumulation of Na + in the leaves of plants which was also obtained in the present study ( Figure 2); it is in agreement with the opinion that high accumulation of Na + in the cytoplasmor chloroplast can affect the integrity and function of photosynthetic membranes, when the vacuole can no longer sequester toxic ions (Bastías et al 2004).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results are in agreement with the findings of Krauss and Allen (2003), suggesting that salinity negatively affects the efficiency of solar energy utilization in S. argentea seedlings. The close relationship between P N and Na + concentration in leaf tissue was reported by Iqbal and Ashraf (2005), indicating that P N was affected by Na + in the leaf mesophyll. Salinity-induced excessive accumulation of Na + in the leaves of plants which was also obtained in the present study ( Figure 2); it is in agreement with the opinion that high accumulation of Na + in the cytoplasmor chloroplast can affect the integrity and function of photosynthetic membranes, when the vacuole can no longer sequester toxic ions (Bastías et al 2004).…”
Section: Discussionsupporting
confidence: 70%
“…High salinity is the most widespread abiotic stress and constitutes the most stringent factor in limiting plant distribution and productivity (Iqbal andAshraf 2005, Yildirim et al 2009). The main negative effects of high salinity that influence plant growth and development are photosynthesis inhibition (Sharma et al 2005), water deficit (Suárez and Medina 2008), ion toxicity associated with excessive Cl -and Na + (Afzal et al 2008, Patel andPandey 2008), interference with nutrition leading to nutrient imbalance (Misra et al 1997).…”
mentioning
confidence: 99%
“…wheat (Iqbal and Ashraf, 2005;Farooq et al, 2011), sunflower (Farooq et al, 2007), rice (Farooq et al, 2008) and tomato (Afzal et al, 2009). Nonetheless, no study has been reported to evaluate the effects of polyamine seed priming on hot pepper.…”
Section: Scientific Notementioning
confidence: 99%
“…However, the protective effects of individual polyamines are somewhat different. For example, Spm and/or Spd was shown to be effective for reversing the inhibitory effect of acid rain (pH 1.8) on bean (Velikova et al 1998(Velikova et al , 2000, mitigating salt injury on wheat (Iqbal and Ashraf 2005), reducing ozonederived injury on potato (Ormord and Beckerson 1986), and enhancing copper tolerance in Nymphoides peltatum (Wang et al 2006). In contrast, Tang and Newton (2005) and Ndayiragije and Lutts (2006) reported that Put was more effective for reducing salt-induced oxidative damage in Virginia pine and alleviating NaCl-derived cell damage in rice, respectively.…”
Section: Effects Of Modulating Endogenous Polyamines On Stress Responsementioning
confidence: 99%